(untitled) (SCIÉNDO INGENIUM, 2024)
The objective of the research was to analyze the evolution, characteristics, and relationships of research in environmental bioremediation of soils contaminated by mining in a period from 2001 to 2024, using VosViewer and Bibliometrix. The results obtained indicated that China is the most productive country with emphasis in areas such as: phytoremediation; followed by Spain which concentrates its research in bioremediation and soils. With co-occurrence analysis, 3 clusters were visualized, one of bioremediation technologies and processes, strategies and challenges of soil remediation, and microbiology and biotechnology in bioremediation. Phytoremediation is considered a core theme, soil, is a declining theme, phragmites australis is a niche theme and the driving themes are translocation factor, acid mine drainage and bioremediation. It was observed that from 2001 to 2013 phytoremediation and bioremediation studies stand out, from 2013 to present phytoremediation, heavy metals and bioremediation studies stand out. Research on environmental bioremediation in soils contaminated by mining is of greater importance since 2007. In conclusion, the study of environmental bioremediation of soils caused by mining is a topic for future research.